2018
DOI: 10.17925/eoh.2018.14.1.40
|View full text |Cite
|
Sign up to set email alerts
|

More than a Gel & Hyaluronic Acid, a Central Component in the Microenvironment of Pancreatic Cancer

Abstract: Hyaluronic acid or hyaluronan (HA) is a major stromal component and its accumulation has been shown to play a central role in promoting tumourigenesis and progression of disease. Thus, overexpression of HA in tumours is associated with poor prognosis. Therapeutic targeting of HA is therefore an attractive strategy, particularly in pancreatic ductal adenocarcinoma (PDA), which is associated with an extremely poor prognosis and less sensitivity towards chemotherapy. PDA is characterised by a high stromal content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…[35] Increasing evidences have suggested that HA, a negatively charged nonsulfated glycosaminoglycan, is abundantly accumulated in tumor surrounding stroma, contributing to an extensive desmoplastic reaction. [36,37] Although the process by which HA accumulated in PDAC stroma is still under investigation, recent proteomic and genomic-based evidences have demonstrated that while both cancer cells and CAFs produce increasing levels of collagens, it was verified that HA is mostly overexpressed by CAFs and it is highly concentrated in the stromal region. [26,36,38] Interestingly, owing to HA role in fibrotic stroma establishment and in hampering anticancer drugs delivery, efforts are being focused on targeting this stroma component by administration of HA-targeting enzymatic agents.…”
Section: Resultsmentioning
confidence: 99%
“…[35] Increasing evidences have suggested that HA, a negatively charged nonsulfated glycosaminoglycan, is abundantly accumulated in tumor surrounding stroma, contributing to an extensive desmoplastic reaction. [36,37] Although the process by which HA accumulated in PDAC stroma is still under investigation, recent proteomic and genomic-based evidences have demonstrated that while both cancer cells and CAFs produce increasing levels of collagens, it was verified that HA is mostly overexpressed by CAFs and it is highly concentrated in the stromal region. [26,36,38] Interestingly, owing to HA role in fibrotic stroma establishment and in hampering anticancer drugs delivery, efforts are being focused on targeting this stroma component by administration of HA-targeting enzymatic agents.…”
Section: Resultsmentioning
confidence: 99%
“…In squamous carcinomas of the head, neck, and skin, the hyaluronan levels are decreased and relate to the neoplasia stage [182]. Increased concentrations are associated with aggressive neoplasms and poor prognoses [184]. Hyaluronidase degrades the ECM and decreases interstitial fluid pressure.…”
Section: Serum Albumin-mediated Systemic Delivery Of Ovsmentioning
confidence: 99%
“…Targeting HA deposition can be divided into 3 approaches: depleting stromal HA, inhibiting HA synthesis, and blocking HA signalling (79). In a mouse model, pegvorhyaluronidase alfa (PEGPH20), the PEGylated form of a recombinant human hyaluronidase, has been shown to deplete or reduce HA within the stroma, thereby improving tumour perfusion and drug delivery (80).…”
Section: Hyaluronic Acidmentioning
confidence: 99%